Spike in Rhino-Orbital-Cerebral Mucormycosis Cases Presenting to a Tertiary Care Center During the COVID-19 Pandemic - Fouad, Yousef A.; Abdelaziz, Tougan Taha; Askoura, Anas; Saleh, Mohamed Ibrahim; Mahmoud, Mohammad S.; Ashour, Doaa Maamoun; Ashour, Manar Maamoun (Frontiers in Medicine, 2021)
Objective: To determine if there was an increase in the rate of cases presenting with rhino-orbital-cerebral mucormycosis (ROCM) to a tertiary care center during the first wave of the COVID-19 pandemic, and the characteristics of the presenting cases. Methods: Retrospective observational study reviewing ROCM cases presenting from March 25th till September 25th, 2020. Cases fulfilling the clinical, radiological, and pathological/microbiological criteria for diagnosis with ROCM were included. Number of cases presenting during the designated interval, their COVID-19 status, comorbidities, and clinical presentation were analyzed. Number of cases during the corresponding interval in the previous 3 years was used as reference to detect if there was a recent spike. Results: Of the 12 ROCM cases identified, 5 had a concurrent positive RT-PCR test result for SARS-CoV-2, 1 had a prior positive result, and 6 did not have concurrent nor prior positive test results. Nine of the 12 cases had poorly controlled diabetes mellitus, and 2 cases had a hematologic malignancy. All cases had orbital invasion and 8 cases had cerebral invasion. The number of cases identified during the interval is much higher than numbers presenting in the prior 3 years during equivalent intervals (range: 1 -2 cases), and than those reported in the literature in different settings in the pre-pandemic era. Conclusions: There is an increased rate of ROCM cases presenting to our center during the first wave of the COVID-19 pandemic. This is a preliminary report and further studies are needed to corroborate the findings and explain possible underlying links.